DIFFERENCES IN MOTOR ABILITIES OF BOYS AND GIRLS OF YOUNGER SCHOOL AGE - Dejan Orlić; Milan Cvetković; Franja Fratrić; Vukašin Badža; Dušan Stupar (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
The battery of 7 motor tests was applied on the sample of 519 boys and 457 girls, 7-10 years of age, from the region of Vojvodina. The results obtained by application of univariant and multivariant analysis of variance indicate that there are certain differences in motor abilities between boys and girls in all younger school ages.